Exchange rate risk and uncertainty and trade flows: Asymmetric evidence from Asia - Mohsen Bahmani-Oskooee; Parveen Akhtar; Sana Ullah; Muhammad Tariq Majeed (Journal of Risk and Financial Management, 2020)
Very recently, the link between exchange rate volatility and trade flows has entered into a new direction in which researchers assess the possibility of asymmetric response of trade flows to a measure of exchange rate uncertainty. We add to this literature by estimating a linear and a nonlinear ARDL model to learn about the experiences of Asian countries, i.e., Pakistan, Japan, China, Korea, Singapore, Malaysia, the Philippines, and India. Like other studies in the literature, nonlinear models yielded relatively more significant results. In some cases, while the linear models showed no significant effects of exchange rate volatility on trade flows, the nonlinear models revealed significant effects. In some other cases, the opposite was true.
Keywords: F31; 330; exchange rate volatility; trade flows; asymmetry effects; Asia